PEMERIKSAAN RISIKO JATUH DAN POSTUR TUBUH SOSIALISASI KOREKSI POSTUR PEMBERIAN LATIHAN BERBASIS RUMAH DAN PELAYANAN FISIOTERAPI PADA LANSIA - Saraswati, P.A.S.; Vittala, G.; Thanaya, S.A.P.; Andayani, N.L.N.; Wibawa, A. (Buletin Udayana Mengabdi, 2024)
Decreased muscle strength, body balance, and changes in body posture in the elderly disrupt the activities of the elderly so that it will have an impact on decreasing productivity and income. The analysis showed that the program needed is to increase muscle strength and balance in the elderly. The implemented programs include screening for fall risk and body posture, socialization of postural correction, home based exercise training and physiotherapy intervention for the elderly. The results showed that the average age of the elderly is 70 years. The balance level of elderly people was categorized as need to be maintained/watched out for. Apart from that, the average score on REEDCO was 76 out of 100, which means poor body posture. This activity was attended by 65 enthusiastic elderly. The elderly understand the importance of postural correction and how to overcome bad posture with the right exercise techniques. After that, physiotherapy services were also provided for elderly people who experienced musculoskeletal disorders by providing physiotherapy modalities in the form of infrared, manual therapy and exercise therapy. At the end of the community service session, outreach and education regarding home based exercise was provided for the elderly to apply at home. Keywords: fall, postural correction, home based exercise, physiotherapy, elderly.